Use of BIM technology for optimization and virtual build of TBM tunnels. Issue 2 (11th April 2022) - Jeon, KiSeok; Dalton, Edward; Bakhshi, Mehdi; Nasri, Verya
Abstract: The practical application of accurate design and coordination in Building Information Modeling (BIM) environment for precast rings in Tunnel Boring Machine (TBM)‐bored tunnels is becoming more achievable. These rings, made up of individual segments, are subject to many constraints which include: 1) deviations from theoretical alignment, as modeling the straight centerline of a ring into a curved alignment naturally produces minor deviations in line and grade, 2) avoiding crucifix joints when the joints between segments align in the longitudinal direction, reducing sealing performance, 3) and TBM shield design by minimizing the diameter of the TBM to reduce overcut and required backfill. This article describes the automated procedures for developing our design intent in the BIM environment with consideration for ring length optimization in tunnel curves, geometrical analyses of the staggered pattern of joints, and the minimum diameter and overcut envelope of the TBM shield. This procedure is demonstrated in multiple light‐rail transit lines in Montréal including the Réseau Express Métropolitain (REM) airport link tunnel and the expansion of the Montreal Blue Line Metro. Virtual build of these segmentally lined tunnels negotiating all straight and curved drives of the alignment with BIM modeling is realized and summarized in this article.